SOCIAL AND PSYCHOLOGICAL PROBLEMS IN INNOVATIVE ACTIVITY OF MODERN RUSSIAN HIGHER EDUCATION INSTITUTION - V. Knyazev (Вестник университета)
Article is devoted to the analysis and the description of the social and psychological problems arising in the course of innovative activity in modern Russian higher education institutions. The description of characteristics of innovative activity and their comparison to conditions of the social and educational environment of higher education institution is submitted.